EFFECT OF PERSON ORGANIZATION FIT AND QUALITY OF WORK LIFE ON ORGANIZATIONAL COMMITMENT MEDIATION OF JOB SATISFACTION - Rita, Winika Santa; RA Marlien, RA Marlien (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Human resource management (HR) is one of the key factors to get the best performance, because in addition to dealing with skills and expertise, HR management is also obliged to build conducive behavior for employees to get the best performance. One of the efforts to get the best performance in human resource management in an organization is by solving problems related to quality and work culture in human resources. In order to increase the organizational commitment of ASN employees at the DPRD Secretariat of Central Java Province, it is necessary to analyze the factors that can support the increase in organizational commitment. In this study where Personal Organizational fit and Quality of Work Life are independent variables, the dependent variable is Organizational Commitment with the mediating variable Job satisfaction. The object of this research is ASN employees at the DPRD Secretariat of Central Java Province. The sample used in this study were 137 respondents who were ASN employees at the DPRD Secretariat of Central Java Province. The results of this study in equation 1 can be seen that partially Person Organizational fit and quality of work life have a significant effect on job satisfaction. While the results of equation 2 can be seen that partially Person Organization fit has no significant effect on organizational commitment, while the variables Quality of work life and job satisfaction have an effect on organizational commitment. The results of the mediation test that there is a mediating effect of job satisfaction on the influence of person organization fit on organizational commitment and there is a mediating effect of satisfaction on the effect of quality of work life on organizational commitment Keywords: Person Organization Fit, Quality of work life, Job satisfaction, Organizational commitment